RANCANG BANGUN SISTEM INFORMASI MAGANG PADA XYZ HOTEL AND CONVENTION CENTER - Grace Philia Luhulima; Sari Prabandari (POLITEKNIK LP3I JAKARTA, 2025)
An internship is a crucial process for prospective employees at a company to prepare them for interacting with other employees and the work they do. During an internship, the company naturally requires a significant amount of data, particularly the interns' data, to be managed efficiently so that it can be used when needed and to maintain completeness. Creating a website is crucial for this data management. The website aims to manage internship registration, recruitment, and monitoring, including attendance. The website uses JavaScript and React programming languages ​​to create the user interface (frontend), PHP for the backend server, MySQL for the database, and Node.js to run the React development server. This website ensures that all internship data is kept complete, confidential, and intact, ensuring the safety of all employees who need it.